CONJUNCTIVE ORGANIC AND MINERAL FERTILIZATION- ITS ROLE IN NUTRIENT UPTAKE AND YIELD OF SOYBEAN UNDER MOLLISOL - MAHENDRA SINGH,; KASTURIKASEN BEURA,; AMIT KUMAR PRADHAN,; NARENDRA KUMAR, (The Bioscan, 2015)
A field experiment was conducted during Kharif 2006-07 and 2007-08 to demonstrate the effect of combined application of organic and mineral fertilizer on the available nutrient status of soil, its translocation in plant and on the subsequent yield of soybean. Ten integrated management modules were evaluated under Mollisols of Tarai region in Randomized block design. The maximum N and P concentration in plants at harvest (8.46 and 7.69% N for 2006 and 2007 respectively and 0.95 and 0.66% P for 2006 and 2007 respectively) was recorded with the treatment FYM @ 5 t ha-1 + Vermicompost (VC) @ 2.5 t ha-1 + Vermiwash (VW) @ 10% + 50% NPK. The same treatment maintained a higher available content of N (285.03 kg ha-1 for 2007 and 291.80 kg ha-1 for 2008) which was significantly higher than the control (i.e. 100% NPK). The maximum grain yields (3209.87 and 3230.88 kg ha-1 in 2006-07 and 2007-08 respectively) was also recorded by the combined application of FYM @ 5 tha-1 +VC @ 2.5tha-1 +VW@ 10% + 50%NPK. Thus it was observed that the treatment consisting of both organic and inorganic nutrient sources performed best among all the treatments used in the experiment.